A DFT/TDDFT mission to probe push–pull vinyl coupled thiophene oligomers for optoelectronic applications1. Issue 62 (8th July 2015) - Gajalakshmi, Duraikannu; Solomon, Rajadurai Vijay; Tamilmani, Venkatachalam; Boobalan, Mariasusai; Venuvanalingam, Ponnambalam
<x xml:space="preserve">Abstract</x> VCTO encompassing pull–pull and push–pull categories has been appraised for fine tuning of band gaps and optoelectronic application through DFT/TDDFT calculations.